Exposure to dust and associated respiratory outcomes among workers at a flour mill in KwaZulu-Natal province, South Africa - Hoopdeo, S; Ghuman, S; Onwubu, SC; Naidoo, V (Occupational Health Southern Africa, 2025)
Background:Inhalation of flour dust is associated with respiratory health effects, but there has been little research conducted on flour mill workers in South Africa. South Africa has an occupational exposure limit (OEL) for grain dust, but no OEL for flour dust. The former is used as the OEL for flour dust, despite the difference in composition and particle size of the two dusts. Flour mill workers report work-related respiratory health effects; therefore, it is essential to establish an OEL for flour dust.Objectives:We assessed reported respiratory symptoms and pulmonary function amongst workers in a flour milling company, and associated factors.Methods:This cross-sectional study was conducted at a flour mill in KwaZulu-Natal province, South Africa, amongst 63 employees: 48 mill workers and 15 office workers. Self-reported symptoms (chest tightness/breathing difficulties, dry cough, sneezing, and running/blocked nose) and work-related factors were elicited in 2021, using a questionnaire. Pulmonary function data were obtained from medical records; personal dust exposures from 2017, 2019, and 2021 were obtained from environmental monitoring reports. Categorical data, including respiratory symptoms and pulmonary function, were summarised using frequencies and percentages. Logistic regression was used to assess the association between exposure and respiratory symptoms, with odds ratios (ORs) and 95% confidence intervals (CIs) reported. Multiple linear regression was used to identify predictors of pulmonary function.Results:The proportions of mill and office workers who reported respiratory symptoms was similar (50.0% and 46.7%, respectively). Mill workers had slightly higher adjusted odds of reported respiratory symptoms than office workers, but this was not statistically significant. In general, the forced expiratory volume in one second/forced vital capacity (FEV1/FVC) ratios of the office workers and the laboratory staff were higher than those of the mill workers in other departments. The FEV1/FVC ratios were slightly higher amongst all participants in 2020, during the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic, than in 2019. Age was a predictor of pulmonary function (β = -0.377 (p = 0.007) in 2019 and β = -0.393 (p = 0.006) in 2020). Some mill workers were exposed to dust at concentrations exceeding the OEL for grain dust.Conclusion:Although mill workers had slightly poorer pulmonary function than office workers, the prevalences of reported respiratory symptoms were similar. However, the high dust exposures in the milling and packing departments indicate that there is a need for improved dust control measures. The establishment of an OEL for flour dust will go a long way to protecting worker health.